Boundary value problem for fractional diffusion equation in a curvilinear angle domain - Pskhu, A.V.; Ramazanov, M.I.; Gulmanov, N.K.; Iskakov, S.A. (KU Publ., 2022)
We consider a boundary value problem for the fractional diffusion equation in an angle domain with a curvilinear boundary. Existence and uniqueness theorems for solutions are proved. It is shown that Holder continuity of the curvilinear boundary ensures the existence of solutions. The uniqueness is proved in the class of functions that vanish at infinity with a power weight. The solution to the problem is constructed explicitly in terms of the solution of the Volterra integral equation.
Қисық сызықты бұрыштық облыстағы бөлшек ретті диффузиялық теңдеу үшін шеттік есеп
Краевая задача для дробного диффузионного уравнения в криволинейной угловой области
Keywords: noncylindrical domain; curvilinear angle domain; boundary value problem; ractional diffusion equation